A semi search algorithm towards semantic search using domain ontologies. (2017) - Khan, Aatif Ahmad; Malik, Sanjay Kumar
In the current Web 2.0 (O'Reilly, 2005), the problem is of efficient retrieval of concerned specific information due to prevalent keyword-based search. Semantic web (Berners-Lee et al., 2001) provides a hope in this direction by providing search based on semantics. Semantic search plays a significant role in retrieving highly relevant search results considering both context and domain information related to posed queries. Semantic search (Guha et al., 2003) can be approached using ontology (Gruber, 1995), which acts as a foundation for incorporating semantics on the web. In this paper, an attempt has been made to propose an approach towards semantic search in the form of a semi search algorithm using domain ontologies for which a semi search tool has been developed for its implementation and evaluation. Key objective of this approach is to return the end user syntactic matching as well as semantically relevant search results. Evaluation results have been obtained which show significant improvements over precision while maintaining a high recall.